Purinergic (ATP) signaling stimulates JNK1 but not JNK2 MAPK in osteoblast-like cells: Contribution of intracellular Ca2+ release, stress activated and L-voltage-dependent calcium influx, PKC and Src kinases - Katz, Sebastian (2008)
This work shows that ATP activates JNK1, but not JNK2, in rat osteoblasts and ROS-A 17/2.8 osteoblast-like cells. In ROS-A 17/2.8 cells ATP induced JNK1 phosphorylation in a dose- and time-dependent manner. JNK1 phosphorylation also increased after osteoblast stimulation with ATPγS and UTP, but not with ADPβS. RT-PCR studies supported the expression of P2Y2 receptor subtype. ATP-induced JNK1 activation was reduced by PI-PLC, IP3 receptor, PKC and Src inhibitors and by gadolinium, nifedipine and verapamil or a Ca2+-free medium. ERK 1/2 or p38 MAPK inhibitors diminished JNK1 activation by ATP, suggesting a cross-talk between these pathways. ATP stimulated osteoblast-like cell proliferation consistent with the participation of P2Y2 receptors. These results show that P2Y2 receptor stimulation by ATP induces JNK1 phosphorylation in ROS-A 17/2.8 cells in a way dependent on PI-PLC/IP3/intracellular Ca2+ release and Ca2+ influx through stress activated and L-type voltage-dependent calcium channels and involves PKC and Src kinases.